Dampak Intervensi terhadap Peningkatan Kepuasan Pernikahan dan Kepuasan Seksual pada Wanita - Widi Lestari; Imami Nur Rachmawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to review interventions that can increase marital satisfaction and sexual satisfaction in women. The method used in this research is a systematic review of databases, namely Scopus, Proquest, SAGE Journal, Taylor and Francis, on published articles from 2012-2022. The total number of reports was 8,058 related articles, and 10 met the inclusion criteria. The results showed that after the intervention, compared to before the intervention, the level of marital satisfaction increased. In contrast, the levels of depression and anxiety decreased significantly in the intervention group (p <0.05), so the intervention could increase marital satisfaction and sexual satisfaction in the intervention and control groups (p < 0.05). In conclusion, interventions to improve interpersonal relationships can also influence a person's coping mechanisms, thereby increasing marital satisfaction and psychological health. Keywords: Intervention, Marital Satisfaction, Sexuality in Women